Intracellular speciation of gold nanorods alters the conformational dynamics of genomic DNA. Issue 12 (December 2018) - Ho, Diwei; Kretzmann, Jessica; Norret, Marck; Toshniwal, Priyanka; Veder, Jean-Pierre; Jiang, Haibo; Guagliardo, Paul; Munshi, Alaa; Chawla, Reena; Evans, Cameron; Clemons, Tristan; Nguyen, Michelle; et al.
Abstract Gold nanorods are one of the most widely explored inorganic materials in nanomedicine for diagnostics, therapeutics and sensing1 . It has been shown that gold nanorods are not cytotoxic and localize within cytoplasmic vesicles following endocytosis, with no nuclear localization2, 3, but other studies have reported alterations in gene expression profiles in cells following exposure to gold nanorods, via unknown mechanisms4 . In this work we describe a pathway that can contribute to this phenomenon. By mapping the intracellular chemical speciation process of gold nanorods, we show that the commonly used Au–thiol conjugation, which is important for maintaining the noble (inert) properties of gold nanostructures, is altered following endocytosis, resulting in the formation of Au(i )–thiolates that localize in the nucleus5 . Furthermore, we show that nuclear localization of the gold species perturbs the dynamic microenvironment within the nucleus and triggers alteration of gene expression in human cells. We demonstrate this using quantitative visualization of ubiquitous DNA G-quadruplex structures, which are sensitive to ionic imbalances, as an indicator of the formation of structural alterations in genomic DNA. The release of nuclear-localizing gold species from intracellular gold nanorods may alter gene expression on interaction with the genomic DNA.